High-resolution patterning of organic semiconductor single crystal arrays for high-integration organic field-effect transistors. (November 2020) - Deng, Wei; Lv, You; Zhang, Xiali; Fang, Xiaochen; Lu, Bei; Lu, Zhengjun; Jie, Jiansheng
Graphical abstract: Abstract: The pursuit of low-cost, high-performance electronic applications with solution-processible organic semiconductors drives the development of efficient methods to pattern organic semiconductor single crystals (OSSCs). However, fluid instabilities and a complex evaporation process have limited patterning of OSSCs with high resolution. Here, we present a solvent-free patterning approach, capillary force-driven molecule flow (CFDMF), to achieve highly aligned 2, 7-dioctyl[1]benzothieno[3, 2-b][1]benzothiophene (C8-BTBT) single crystal patterns with sub-micron resolution and high fidelity. The position as well as pattern shape and resolution of the C8-BTBT single crystal arrays can be predetermined through photolithography. Using this method, we have demonstrated a high-integration circuit comprising over 169 organic field-effect transistors (OFETs) with a high resolution of 310 dpi. The resultant OFETs show good field-effect properties with an average mobility of 4.44 cm 2 V −1 s −1 . This patterning technique constitutes a major step toward the use of the high-mobility OSSCs for integrated device applications.